2000
DOI: 10.2105/ajph.90.8.1254
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of drinking and cognitive performance in elderly Japanese American men: the Honolulu-Asia Aging Study

Abstract: OBJECTIVES: This study prospectively describes the relationships between alcohol intake and subsequent cognitive performance among participants in the Honolulu Heart Program (HHP). METHODS: Alcohol intake was assessed at Exam III of the HHP, and cognitive performance was measured approximately 18 years later with the Cognitive Abilities Screening Instrument (CASI). Complete information was available for 3556 participants, aged 71 to 93 years at follow-up. RESULTS: In multivariate analyses, the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…These unadjusted associations show that this dataset had enough power to detect significant associations. These unadjusted associations are also consistent with several prior studies that showed worse cognitive performance among those who do not drink alcohol or have stopped drinking alcohol (e.g., 2326, 28, 30, 31, 39 ), compared to those who currently drink alcohol. However, these unadjusted associations were eliminated after controlling for the variables that we presented in Figure 2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These unadjusted associations show that this dataset had enough power to detect significant associations. These unadjusted associations are also consistent with several prior studies that showed worse cognitive performance among those who do not drink alcohol or have stopped drinking alcohol (e.g., 2326, 28, 30, 31, 39 ), compared to those who currently drink alcohol. However, these unadjusted associations were eliminated after controlling for the variables that we presented in Figure 2.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have shown that current alcohol users have better cognitive performance than former alcohol users or those who have never used alcohol 2328 . Whether alcohol affects cognitive performance also depends on many other factors, such as sex 2934 , dose of alcohol 3539 and length of abstinence 40 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this strategy did not succeed in identifying a significant benefit for Hungary (compare hungary and hungary-nh lines) or for Japan (compare japan and japan-nh lines). However, in the case of Japan it should be noted that two studies of Japanese Americans (japan-amer)114,148 did find a significant benefit of alcohol, suggesting failure to find a significant benefit in the studies in Japan may not have a genetic basis. In addition, one “no ratio” study of Japanese Americans found better cognition in moderate drinkers 79.…”
Section: Resultsmentioning
confidence: 97%
“…For example, a much-replicated finding in social epidemiology holds that older persons who drink alcohol moderately perform better on cognitive assessments than those who either abstain or drink to excess, thus suggesting a beneficial effect of drinking in moderation (Christian et al, 1995; Elias, Elias, D’Agostino, Silbershatz, & Wolf, 1999; Galanis et al, 2000; Goodwin et al, 1987; Hebert et al, 1993; Hendrie, Gao, Hall, Hui, & Unverzagt, 1996; Launer, Feskens, Kalmijn, & Kromhout, 1996). Unfortunately, these studies share designs with poor control of prior cognitive ability.…”
Section: Ability Across the Life Coursementioning
confidence: 99%